2015
DOI: 10.5123/s1679-49742015000400009
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à reincidência de gravidez após gestação na adolescência no Piauí, Brasil

Abstract: Objetivo: analisar fatores associados à reincidência de gravidez após gestação na adolescência. Métodos: estudo transversal realizado na capital e em cinco cidades do interior do Piauí, Brasil, em 2008-2009; foram calculadas odds ratios (OR) e intervalos de confiança de 95% (IC 95% ). Resultados: foram entrevistadas 639 mulheres de 17 a 22 anos de idade; 87,9% delas tiveram a primeira gestação entre 15 e 19 anos; a prevalência de reincidência de gravidez no período de dois anos após o término de uma gestação f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 9 publications
2
14
0
12
Order By: Relevance
“…12 In our sample, the mean time to a new pregnancy was 28.9 months, with an RRP rate of 26.8% (30/112). This value is similar to the 25.9% (120/464) found by Nery et al 20 in young mothers aged between 17 and 22 years in the city of Teresina (capital of the state of Piauí) and the 35.4% (62/175) detected by Nery et al 21 in five municipalities in the state's countryside. A study with data from the declarations of live births in the city of Rio de Janeiro, for the year 2002, identified an RRP rate of 5.2% (809/15,636) in adolescents aged between 10 and 19 years.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…12 In our sample, the mean time to a new pregnancy was 28.9 months, with an RRP rate of 26.8% (30/112). This value is similar to the 25.9% (120/464) found by Nery et al 20 in young mothers aged between 17 and 22 years in the city of Teresina (capital of the state of Piauí) and the 35.4% (62/175) detected by Nery et al 21 in five municipalities in the state's countryside. A study with data from the declarations of live births in the city of Rio de Janeiro, for the year 2002, identified an RRP rate of 5.2% (809/15,636) in adolescents aged between 10 and 19 years.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, formal education is presented as the main variable to solve the social problem of teenage pregnancy. 21 Our research has shown that every additional year of study in a girl's life provides increased protection against recurrence of pregnancy. This finding is in agreement with the scientific literature that assumes that the longer the girls continue to study, the more topics related to sexuality are addressed, allowing their empowerment regarding contraceptive methods.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations